Communicative Responses Of Students To Campus Life Pressures - Yulia Putri Maharani; Alifzu Raja Tegar Julianda; Jordy Ardiansyah; Sri Narti (Universitas Dehasen Bengkulu, 2026)
University students are in a phase of life characterized by various academic, economic, and social demands that may create pressures within campus life. These pressures require students to adapt and develop ways to respond to challenging situations through everyday communication. This study aims to examine the communicative responses of university students in Bengkulu to campus life pressures. The research employed a qualitative approach using a descriptive method. Data were collected through in-depth interviews, observation, and documentation involving active students from various study programs at several universities in Bengkulu Province. The findings indicate that students experience academic pressure related to coursework demands and achievement expectations, economic pressure associated with financial limitations, and social pressure related to adjustment processes within the campus environment. These pressures shape students’ communicative responses, which tend to be practical, adaptive, and solution-oriented. Students often use direct and efficient communication to express needs and seek solutions to the challenges they face. Interpersonal communication among peers serves as a primary medium for sharing experiences and obtaining support, while communication between students and lecturers plays an important role in managing academic pressure. In addition, students adjust their communication styles based on context and interlocutors and utilize digital media to access information and maintain social relationships. This study highlights that students’ communicative responses represent an essential part of the adaptation process to campus life pressures.